Identity integration in Steven Spielberg's Catch Me If You Can (2002) - Rizky Apriyanto (Journal of Research on English and Language Learning (J-REaLL), 2022)
The purpose of this paper is to examine the four types of identity integration and the affection to the main character in Steven Spielberg's film Catch Me If You Can (2002). It elucidates the psychological illness that led to the main character's multiple identities in the film. Identity is a complicated topic these days, and it has become one of the most debated topics. Frank William Abagnale Jr., the primary character in this story, is a promising young man with complicated family concerns. As a result, various issues during Frank's adolescence contributed to his psychological condition. The research is a psychoanalytic analysis that employs Erik Erikson's (1902)psychological theory as well as Warren Buckland's (1966) and Timothy Heiderich's cinematographic language. The findings show that Frank William Abagnale Jr. suffers from a psychological condition. His symptoms of identity disintegration are primarily due to a family situation that he was dealing with at the time of his adolescence, and it has an impact on his future. He must impersonate other people's identities in order to overcome his breakdown. As a result, Frank William Abagnale Jr., the movie's main character, is insane since he gets millions of dollars before he is nineteen.